Electrofishing as a new method to search for unknown populations of the endangered freshwater pearl mussel Margaritifera margaritifera - Salonen, Jouni; Taskinen, Jouni (Aquatic Conservation: Marine and Freshwater Ecosystems, 2017)
1. The freshwater pearl mussel Margaritifera margaritifera is threatened throughout its Holarctic range, but the occurrence of this species is insufficiently mapped. For the conservation of M. margaritifera, it is important to identify populations more comprehensively. 2. Traditionally mussels have been searched for visually using techniques such as diving and aquascope, both of which are potentially time-consuming and demanding survey methods. 3. In this study, a new search method is presented. As glochidia of M. margaritifera are larval parasites on gills of salmonid fish, electrofishing and non-destructive examination of salmonids with the naked eye may reveal the presence of glochidia and therefore the occurrence of M. margaritifera in watercourses. This method was tested in both the field and laboratory in northern Finland. 4. In summer, when M. margaritifera glochidia were large, the status of salmonids being infected or uninfected by M. margaritifera was correctly identified with the naked eye with 62, 80, 88 and 93 % accuracy in four streams sampled, 96 % accuracy in the laboratory, and 100 % accuracy in all cases when at least 20 glochidia per fish were present. Intensity of infection was also assessed successfully; a specifically tailored, qualitative abundance score correlated significantly with the real number of glochidia. However, during autumn with small glochidia freshly attached to fish, glochidia infection could be observed only under microscopic examination. 5. When the method was used in 40 previously incompletely surveyed tributaries, three M. margaritifera populations were found. The infection in salmonids was observed always with the naked eye, being subsequently confirmed microscopically. The existence of adult mussels in two of these rivers was also confirmed. 6. The results indicate that electrofishing and a relatively quick naked-eye check of salmonids provides a new, non-destructive, and potentially cost-effective way to search for new, previously unrecorded M. margaritifera ...